Abnormal FDG and MIBG Activity in the Bones in a Patient With Neuroblastoma Without Detectable Primary Tumor. (August 2016) - Zhang, Wei; Zhuang, Hongming; Servaes, Sabah
Abstract : Abstract: Neuroblastoma is among the most common extracranial solid tumors in pediatric patients and typically arises anywhere from the neck to pelvis but most commonly in the adrenal glands. It is extremely rare for a patient to have extensive metastases from neuroblastoma without primary tumor being identified. We present a 3-year-old with widespread bone and bone marrow involvement of the disease revealed on both FDG PET/CT and MIBG scan, which was pathologically proven as neuroblastoma. However, extensive imaging did not detect primary tumor anywhere.